Supporting 3D modeling in the academic library. Issue 2 (19th June 2017) - Radniecki, Tara
Abstract : Purpose: An increased number of academic libraries are providing access to nontraditional technologies including 3D printers, 3D scanners, laser cutters, and more. However, these new equipment offerings require users to learn new literacies and skills in order to fully utilize them and realize their full potential to impact creativity and innovation on campus. The purpose of this paper is to share how one academic library is providing services and resources to help users acquire the necessary 3D modeling skills to design and successfully 3D print new knowledge objects. Design/methodology/approach: The library is providing access to online tutorials on many different 3D modeling programs, gives instruction on 3D modeling through group workshops, and provides individual consultations with 3D modeling experts. These instruction efforts were assessed by analyzing usage statistics, attendance, and user satisfaction surveys. Findings: Usage statistics show that the online tutorials are heavily utilized by UNR users and that many different 3D modeling programs are of interest to our community. Usage statistics and user surveys show the individual consultation service to be helpful and often exceeding expectations. Workshop attendance is generally low and appears to positively impact far fewer users than the other services. Originality/value: While more libraries begin providing access to maker technologies, few are addressing the need to teach new skills and literacies necessary to utilize those technologies fully. This paper may prove valuable for other academic libraries to start providing avenues of learning for new and nontraditional library skills, such as 3D modeling.